Social exclusion and inclusion: The shape of water (2017) = Loại trừ và hội nhập xã hội: bộ phim “The shape of water” (2017) - Bùi, Thu Thuỷ (2021)
This humanities-oriented research explores a phenomenon called “Social exclusion and inclusion” that arose in economic discourse in Europe in 1960s, and eventually become a human rights issue during 1990s. The aim of this research is to analyze the origins and progress of social exclusion and inclusion in the film industry of Hollywood, with a particular case of The shape of water (2017), 2018 Oscar winner for “Best picture of the year”. By using semiotics, the method which is quite familiar in cultural studies, the paper makes sense of social exclusion and inclusion in the theme of monster romance movies. To clarify the case, similar techniques are addressed to research on how the movie contributes to the knowledge and representation of social exclusion and inclusion. This thesis reveals that although The shape of water is set on a familiar script, it provides a new perspective of the connection between human and monsters, and the relation between exclusion and inclusion.